Seeing the Beatific Vision in "Good Friday: Made as I was Riding Westward that Day" through John Donne's Sermons - Cefalu, Paul (Christianity & literature, 2019)
This article compares John Donne's sermonic treatment of the beatific vision to the related but divergent treatment of the theme in his poem "Good Friday: Made as I was Riding Westward that Day." Never one simply to duplicate in his poetic imaginings the pure, if occasional, theology of the sermons, Donne suggestively strays from the sermonic line on seeing God's face in his most extended and provocative meditative poem on the theme, "Good Friday."